Ageing with a twist: Intimacy and care amongst LGB older adults in Portugal - Santos, Ana Cristina (2023)
Accepted version of the article: Santos, Ana Cristina (2023), "Ageing with a twist: Intimacy and care amongst LGB older adults in Portugal", Portuguese Journal of Social Science, 20, 3, 171-184. DOI: https://doi.org/10.1386/pjss_00040_1